# Integration of rational functions.

Don’t worry if people think you’re crazy. You are crazy. You have that kind of intoxicating insanity that lets other people dream outside of the lines and become who they’re destined to be, Jennifer Elisabeth, Born Ready: Unleash Your Inner Dream Girl.

# Partial fraction decomposition: Distinct linear factors

$\int (\frac{1}{x-4} + \frac{2}{x+3})dx = ln|x-4| + 2ln|x+3| + C.$

The cover-up method is a technique used for finding the coefficients in the partial fraction decomposition of a rational function, say $\frac{P(x)}{Q(x)}$. The denominator of the rational function should factor into distinct linear factors and deg(P) < deg(Q).

1. Factorize the denominator of the rational function into linear and irreducible quadratic factors, e.g., $\int \frac{4x-1}{x^2+x-2}dx = \int \frac{4x-1}{(x-1)(x+2)}dx$
2. Write or express the rational function as a sum of partial fractions, e.g., $\frac{4x-1}{(x-1)(x+2)} = \frac{A}{x-1} + \frac{B}{x+2}$.
3. Solve for the constants, e.g., solve for A by multiplying by (x-1), $\frac{4x-1}{(x+2)} = A + \frac{B(x-1)}{(x+2)}$ ⇒[For the factor x-1, set x = 1] $\frac{4-1}{1+2} = A + 0$ ⇒ A = 1; solve for B by multiplying by (x +2), $\frac{4x-1}{(x-1)} = \frac{A}{x-1}(x+2) + B$ ⇒ [For the factor x+2, set x = -2] $\frac{-8-1}{-2-1} = B$ ⇒ B = 3.
4. Integrate each term obtained from the partial fraction decomposition, $\int \frac{4x-1}{x^2+x-2}dx = \int \frac{1}{x-1}dx + \int \frac{3}{x+2}dx = ln|x-1|+3ln|x+2| + C$ where C is the constant of integration.
• $\int \frac{1}{(x-2)(x-3)}dx$

$\frac{1}{(x-2)(x-3)} = \frac{A}{x-2} + \frac{B}{x-3}$ ⇒[solve for A by multiplying by (x-2)] $\frac{1}{(x-3)} = A + \frac{B(x-2)}{x-3}$ ⇒[set x = 2] $\frac{1}{-1} = A$ ⇒ A = -1. Analogously, [solve for A by multiplying by (x-3)] $\frac{1}{(x-2)} = \frac{A(x-3)}{x-2} + B$ ⇒[set x = 3] B = 1.

$\int \frac{1}{(x-2)(x-3)}dx = -\int \frac{1}{x-2}dx +\int \frac{1}{x-3}dx = -log|x-2| + log|x-3| + C.$

# Partial fraction decomposition: Repeated linear factors

Let’s see a more complicated example when the denominator Q has a repeated linear factor, e.g., $\int \frac{x^2+2}{x^3-3x+2}dx = \int \frac{x^2+2}{(x-1)^2(x+2)}dx$. The partial fraction decomposition is of the form: $\frac{x^2+2}{(x-1)^2(x+2)} = \frac{A}{x-1} + \frac{B}{(x-1)^2} + \frac{C}{x+2}$.

To obtain C, we multiply by (x+2), $\frac{x^2+2}{(x-1)^2} = \frac{A(x+2)}{x-1} + \frac{B(x+2)}{(x-1)^2} + C$, then set x = -2, $\frac{(-2)^2+2}{(-2-1)^2} = C, C = \frac{2}{3}$.

To obtain B, we multiply by (x-1)2, $\frac{x^2+2}{(x+2)} = A(x-1) + B + \frac{C(x-1)^2}{x+2}$, then set x = 1, $\frac{1^2+2}{1+2} = B$ ⇒ B = 1. This method does not work for the constant A.

Finally, we set x = 0, $\frac{2}{(-1)^2·2} = \frac{A}{-1} + \frac{B}{(-1)^2}+\frac{C}{2}$ =[B = 1, C = 2/3] $1 = \frac{A}{-1} + \frac{1}{(-1)^2}+\frac{2/3}{2}$ ⇒ 1 = -A +1 +1/3, A = 13.

$\int \frac{x^2+2}{x^3-3x+2}dx = \int \frac{x^2+2}{(x-1)^2(x+2)} = \int \frac{1/3}{x-1} +\frac{1}{(x-1)^2} + \frac{2/3}{x+2} dx = \frac{1}{3}ln|x-1| -\frac{1}{x-1} + \frac{2}{3}ln|x+2| + C.$

• $\int \frac{x+1}{(x-1)^3(x-2)}dx$

$\frac{x+1}{(x-1)^3(x-2)}dx = \frac{A}{x-1} + \frac{B}{(x-1)^2} + \frac{C}{(x-1)^3} + \frac{D}{x-2}$ [1]

To obtain C, we multiply by (x-1)3, $\frac{x+1}{(x-2)} = A(x-1)^2 + B(x-1) + C + \frac{D(x-1)^3}{x-2}$, then set x = 1, C = $\frac{1+1}{1-2} = -2.$

To obtain D, we multiply by (x-2), $\frac{x+1}{(x-1)^3} = \frac{A(x-2)}{x-1} + \frac{B(x-2)}{(x-1)^2} + \frac{C(x-2)}{(x-1)^3} + D$, then set x = 2, D = $\frac{2+1}{(2-1)^3}=3$

Finally, combining the terms of [1],

$x +1 = A(x-1)^2(x-2) + B(x-1)(x-2) + C(x-2) +D(x-1)^3 = A(x^3-4x^2 + 5x − 2) + B(x^2 − 3x + 2) + C(x − 2) + D(x^3 − 3x^2 + 3x − 1) = (A + D)x^3 + (−4A + B − 3D)x^2 + (5A − 3B + C + 3D)x − 2A + 2B − 2C − D$,

and obtain the following equations,

A + D = 0 ⇒ A = -D = -3
−4A + B − 3D = 0 ⇒ 12 +B -9 = 0 ⇒ B = -3. \

$\int \frac{x+1}{(x-1)^3(x-2)}dx = \int \frac{-3}{x-1}dx + \int \frac{-3}{(x-1)^2}dx + \int \frac{-2}{(x-1)^3}dx + \int \frac{3}{x-2}dx = -3log|x-1|+\frac{3}{x-1}+\frac{1}{(x-1)^2}+3log|x-2|+C.$

• $\int \frac{x^2}{x^3-x^2+x-1}dx = \int \frac{x^2}{(x-1)(x^2+1)}dx$

The partial fraction decomposition is of the form: $\frac{x^2}{(x-1)(x^2+1)} = \frac{A}{x-1}+\frac{Bx + C}{x^2 +1}$.

Cover up for A is quite the same process, by multiplying for (x -1), $\frac{x^2}{(x^2+1)} = A +\frac{(Bx + C)(x-1)}{x^2 +1}$, then set x = 1, $\frac{1^2}{1^2+1} = A ⇒ A = \frac{1}{2}.$

Cover up for B and C is done by clearing the denominator, $x^2 = A(x^2+1) + (Bx+C)(x-1) = \frac{1}{2}(x^2+1) + (Bx+C)(x-1)$. x2 term, $1 = \frac{1}{2} + B ⇒ B = \frac{1}{2}$, and the constant term $0 = \frac{1}{2} -C ⇒ C = \frac{1}{2}$.

$\int \frac{x^2}{(x-1)(x^2+1)}dx = \int \frac{\frac{1}{2}}{(x-1)}dx + \int \frac{\frac{x}{2}}{(x^2+1)}dx + \int \frac{\frac{1}{2}}{(x^2+1)}dx= \frac{1}{2}ln|x-1| + \frac{1}{4}ln(x^2+1) + \frac{1}{2}tan^{-1}x + C~ because~ \frac{d}{dx}ln(x^2+1)=\frac{2x}{x^2+1}.$

$\int \frac{x}{(x^2+4)^3}dx$ =[u = x2+4, du = 2xdx] = $\int \frac{1}{2(u)^3}du = \frac{1}{2}\frac{u^{-2}}{-2}+C = \frac{-1}{4}u^{-2}+C = \frac{-1}{4(x^2+4)^2}+C$

# Integration of improper rational fraction.

An improper rational fraction refers to a rational function where the degree of the numerator is greater than or equal to the degree of the denominator, e.g., $\frac{x^2}{x+1}, \frac{x^3}{(x-1)(x+2)}=\frac{x^3}{x^2+x-2}$.

• $\int \frac{x^2}{x+1}dx$

Let’s apply long division,

• $\int \frac{x^2}{x+1} = \int (x-1+\frac{1}{x+1})dx = \frac{1}{2}x^2 -x + log|x+1| + C.$

• $\int \frac{x}{x+1}dx$ =[long division] $\int (1-\frac{1}{x+1})dx = x -log|x+1| + C.$

To calculate $\int \frac{x^3}{x^2+x-2}dx$, let’s apply long division,

$\int \frac{x^3}{x^2+x-2}dx = \int x - 1 + \frac{3x -2}{x^2 +x -2} dx$

Let’s factor the denominator x2+x-2 = (x +2)(x -1), $\frac{3x -2}{x^2 +x -2} = \frac{A}{x+2} + \frac{B}{x-1}$. To calculate A and B, we multiply for (x+2) and (x-1) respectively. $\frac{3x -2}{x -1} = A + \frac{B(x+2)}{x-1}$, set x = -2, $\frac{-6-2}{-2-1} = A ⇒ A = \frac{8}{3}$. Similarly, $\frac{3x -2}{x +2} = A\frac{x-1}{x+2} + B$, set x = 1, B = $\frac{3-2}{1+2} = \frac{1}{3}$

$\int \frac{x^3}{x^2+x-2}dx = \int x - 1 + \frac{3x -2}{x^2 +x -2} dx = \int x - 1 + \frac{\frac{8}{3}}{x+2} + \frac{\frac{1}{3}}{x-1} dx = \frac{1}{2}x^2 -x + \frac{8}{3}ln|x+2| +\frac{1}{3}ln|x-1| + C.$

# Bibliography

This content is licensed under a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License and is based on MIT OpenCourseWare [18.01 Single Variable Calculus, Fall 2007].
1. NPTEL-NOC IITM, Introduction to Galois Theory.
2. Algebra, Second Edition, by Michael Artin.
3. LibreTexts, Calculus. Abstract and Geometric Algebra, Abstract Algebra: Theory and Applications (Judson).
4. Field and Galois Theory, by Patrick Morandi. Springer.
5. Michael Penn, and MathMajor.
6. Contemporary Abstract Algebra, Joseph, A. Gallian.
7. YouTube’s Andrew Misseldine: Calculus. College Algebra and Abstract Algebra.
8. MIT OpenCourseWare 18.01 Single Variable Calculus, Fall 2007 and 18.02 Multivariable Calculus, Fall 2007.
9. Calculus Early Transcendentals: Differential & Multi-Variable Calculus for Social Sciences.
Bitcoin donation

JustToThePoint Copyright © 2011 - 2024 Anawim. ALL RIGHTS RESERVED. Bilingual e-books, articles, and videos to help your child and your entire family succeed, develop a healthy lifestyle, and have a lot of fun.